TANGGUNG JAWAB NOTARIS ATAS PENGGUNAAN DOKUMEN PALSU DALAM PEMBUATAN AKTA AUTENTIK - Iis Laila Ridawati; Endang Purwaningsih; Irwan Santosa (Res Justitia : Jurnal Ilmu Hukum, 2023)
Notary Public Law determines that a notary is a public official authorized to create authentic deeds. It is responsibility in correct way to notarized the administered document. The falsification of a document may results in the deed becoming inauthentic. Formulation of this issue to analyze notary responsibility for the use of false documents in the creation of authentic deed and legality of authentic deed of false documents against parties and third parties. The method used normative-empirical and statute approach supported in depth interview. Based on the results of the research concluded notary responsibility for the use of false documents in the authentic deed carried out dismissal by the Minister, subject to the threat of imprisonment stipulated in Article 21 Paragraph (2) Decree of the Minister of Justice and Human Rights of the RI Number M-01. HT.03.01 Year 2003; and the legality of the authentic deed of false documents against the parties and third parties, the deed does not decrease the level or degradation into an underhand deed because the requirements formal of the deed are met. If throughout the litigation process is known and proven then there is a possibility of the judge to decide that the deed is no longer valid among the parties but the form of the deed remains authentic pursuant to Article 84 of Law No. 2 of 2014 Amendments to Law No. 30 of 2004 Notary Public.